Intelligent Information and Database Systems 7th Asian Conference, ACIIDS 2015, Bali, Indonesia, March 23-25, 2015, Proceedings, Part I - Nguyen, Ngoc Thanh; Trawiński, Bogdan; Kosala, Raymond (Lecture Notes in Artificial Intelligence,, 2015)
The two-volume proceedings of the ACIIDS 2015 conference, LNAI 9011 + 9012, constitutes the refereed proceedings of the 7th Asian Conference on Intelligent Information and Database Systems, held in Bali, Indonesia, in March 2015. The total of 117 full papers accepted for publication in these proceedings was carefully reviewed and selected from 332 submissions. They are organized in the following topical sections: semantic web, social networks and recommendation systems; text processing and information retrieval; intelligent database systems; intelligent information systems; decision support and control systems; machine learning and data mining; multiple model approach to machine learning; innovations in intelligent systems and applications; bio-inspired optimization techniques and their applications; machine learning in biometrics and bioinformatics with applications; advanced data mining techniques and applications; collective intelligent systems for e-market trading, technology opportunity discovery and collaborative learning; intelligent information systems in security and defense; analysis of image, video and motion data in life sciences; augmented reality and 3D media; cloud based solutions; internet of things, big data and cloud computing; and artificial intelligent techniques and their application in engineering and operational research.